Transgenic Expression of Polyomavirus Middle T Antigen in the Mouse Prostate Gives Rise to Carcinoma - Lee, Sang Hyun (American Society for Microbiology, 2011)
The middle T (MT) antigen of polyomavirus has provided fundamental insights into the regulation of mammalian cell growth in vitro and important animal models for the analysis of tumor induction. The mouse mammary tumor virus (MMTV)-MT model of breast cancer has been important for probing the cellular signaling pathways in mammary tumorigenesis. MT itself has no intrinsic enzymatic activity but, rather, transforms by binding to and activating key intracellular signaling molecules, phosphatidylinositol 3-kinase (PI3-kinase) being the best studied of these. Thus, MT mimics a constitutively activated receptor tyrosine kinase (RTK). Our recent work suggests that MT signaling, like that of RTKs, is often quite dependent on cellular context in vitro. Here, we examine contextual effects on signaling in animal models as well. In this study, we generated transgenic mice in which MT is expressed in the mouse prostate under the control of an (ARR)2-Probasin promoter. All male transgenic mice displayed mouse prostatic intraepithelial neoplasia (mPIN) in the ventral and dorsal/lateral prostate as early as 8 weeks of age. Notably, during the course of tumor development over time, invasive cancer, reactive stroma, and infiltration of inflammatory cells were seen. Transcriptional profiling analyses show regulation of multiple pathways, with marked upregulation of both the NF-κB and inflammatory pathways. Comparison of expression profiles of our MT prostate model with those from an MMTV-MT breast model (23) shows both tissue-specific and tissue-independent MT effects. The signature of genes regulated by MT in a tissue-independent manner may have prognostic value.